Bulletin. - Maharashtra (India). Sales Tax Dept.; Maharashtra (India). (Bombay : Director, Govt. Printing and Stationery, Maharashtra State., 1960)
Includes legislation.
Mode of access: Internet.
Issued by the department's Public Relations Officer.
Keywords: Sales tax -- India -- Maharashtra